SOS: A Framework for Software Reuse over Open Networks - Silveira, Glêdson Elias da; Meira, Silvio Lemos (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2000)
Software engineering research has demonstrated that software reuse can lead to higher productivity, better quality and smaller time to market. In addition, it is known that the benefits increase when reuse is carried out across multiple systems. projects, and even organizational boundaries. In such scenario, where components must be delivered to geographically distributed producers in short time and at low cost, traditional in-house libraries of reusable components are absolutely unsatisfactory. This paper introduces SOS (Software Operating System), a framework for supporting on demand, dynamic distribution and integration of distributed, versioned, reusable components on both producers and users environments. The framework combines hypertext-based Web concepts and mobile code abstractions to define a transparent, distributed component library, which defines the basis for large scale, systematic reuse of software components during development, deployment, execution and evolution of software systems.